Critical Success Factors (CSFs) of Contractor in Industrialised Building System (IBS) Implementation - Shahrul Fazry Bin Abdullah Sani, Shahrul Fazry (Universiti Teknologi Petronas, 2010)
this paper is identifying and ranking the Critical Success Factors (CSFs) for contractors in implementing lBS and also creating a project management guideline for contractor in order to implement IBS. This is done by relating the CSFs and the basic concept of construction project management. In general, the CSFs highlighted from both literatures and interview session from pilot survey are categorised as business strategies, finance, partnering and contract, enabling factors, roles and in-house manufacturing, lean and advanced planning, skills, process management and finally training and education.